2017
DOI: 10.5830/cvja-2016-093
|View full text |Cite
|
Sign up to set email alerts
|

Atrial myxoma: a rare cause of hemiplegia in children

Abstract: SummaryBackground:Atrial myxoma is an uncommon cause of hemiplegia in children. However hemiplegia is the commonest manifestation of atrial myxoma in the paediatric age group.Case report:An 11-year-old girl presented with left hemiplegia and palpitations. Three months later she had a deepvein thrombosis of the right common iliac vein. MRI of the brain showed a subacute right thalamic infarct, and an ECG showed left atrial and left ventricular hypertrophy. Transthoracic echocardiography revealed a left atrial m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
(9 reference statements)
1
8
0
Order By: Relevance
“…These findings suggest the protective role of vitamin D [95] (Figure 2). However, no independent association was found between low vitamin D levels and AF after coronary artery bypass surgery [96]. Similarly, the Atherosclerosis Risk in Communities (ARIC) study did not find any significant association between low levels of vitamin D and incident AF in a community-based cohort and in a meta-analysis of prospective studies comprising 12,303 subjects.…”
Section: Cardiac Diseasesmentioning
confidence: 99%
“…These findings suggest the protective role of vitamin D [95] (Figure 2). However, no independent association was found between low vitamin D levels and AF after coronary artery bypass surgery [96]. Similarly, the Atherosclerosis Risk in Communities (ARIC) study did not find any significant association between low levels of vitamin D and incident AF in a community-based cohort and in a meta-analysis of prospective studies comprising 12,303 subjects.…”
Section: Cardiac Diseasesmentioning
confidence: 99%
“…A key action recommended in the plan to eradicate RHD inAfrica includes appropriate training of health workers to safelyand effectively deliver BPG. 22 The preliminary experience in Zambia suggests that appropriate educational interventions in the setting of drug availability and ready access to medications to treat anaphylaxis can positively impact on rates of BPG usage. Future work will involve the exploration of innovative ways to scale up the RHD control programme, such as the use of electronic training modules, and determination of the impact of these types of interventions on health outcomes, including the incidence of RF and RHD.…”
Section: Discussionmentioning
confidence: 99%
“… 18 - 20 The reasons for this are complex and related to a multitude of interacting factors, including drug supply, pharmaco-economics, health service infrastructure and possibly socio-cultural drivers. 21 Indeed, a recent high-level report outlining the key actions required to eradicate RHD in Africa identified variable supply and suboptimal quality and use of penicillin as some of the major barriers to achievement of this goal, 22 a position endorsed by the World Heart Federation. 23 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6] According to our review of relevant literature, no such cases were reported in in the last 10 years possibly because of a substantial decline in the incidence of rheumatic heart disease. Myxomas are most commonly located in the left atrium, originate from the fossa ovalis, and present with symptoms of thromboembolism [7] or mitral valve outflow obstruction. [8] Constitutional symptoms include fever, weight loss, arthralgias, anemia, elevated globulins and sedimentation rate which could mimic infective endocarditis, particularly with mitral stenosis.…”
Section: Discussionmentioning
confidence: 99%